Raising Awareness About the Risk of Irregular Migration: Quasi-Experimental Evidence from Guinea - Jasper Tjaden; Horace Gninafon (Population and Development Review, 2022)
In response to mounting evidence of harm inflicted on irregular migrants along their journeys from West Africa to Europe, international organizations, civil society organizations, and governments have scaled up campaigns as a tool for raising awareness about the risks of irregular migration. Campaigns aim to counter misinformation by smugglers and facilitate safe migration decisions. Despite the growing number of interventions, there is limited empirical evidence on the impact and effectiveness of such campaigns. Based on a difference-in-difference design, this study investigates the effect of a mobile cinema and community discussion intervention on the perceptions, knowledge, and intentions of potential irregular migrants in Northern Guinea in 2019. The results show that potential migrants who participated in events were significantly more likely to show awareness gains and less likely to report high intentions to migrate irregularly. While the relative importance of risk perceptions and their impact on migration flows remain unclear, the findings provide evidence supporting the assumption that risk awareness can be a relevant factor in the decision-making process of potential irregular migrants. While campaigns may be an effective tool in certain contexts, effect sizes highlight the need for policymakers to keep realistic expectations.
Keywords: 300; irregular migration; risk; campaign; decision; West Africa